Living Learning Resources Management of Ban Tha Sab School Group, Yala Province - Treepaiboon, Naowarat (Area Based Development Research Journal, 2019)
The research study aims to propose guidelines for living learning resource management of Ban Tha Sab school group, Muang district, Yala province. The purposive samplings are 42 people, namely students, teachers, library staff and school administrators, from 3 schools including Ban Tha Sab school, Ban Sa Kho school and Ban Li Mud school (Boonchop Sakarin). The implementation of 4 participatory processes consists of 1) analyzing the problems, 2) planning for problem-solving, 3) implementing the plan, and 4) evaluating the processes performed for change. Three activities undertaken to create change include (1) Promoting learning resources in schools by developing Ban Tha Sab school group’s living learning resources, (2) Promoting external resources for learning available in Rajabhat Yala University, and (3) Monitoring and evaluating the living learning resources management. The findings indicate that: 1) the newly-arranged library environment as a living learning resource increases the frequency of library visits; 2) the enhancement of living learning activities resources (both internal and external) instills the students’ habits for pursuing knowledge; and 3) the potential networking for living learning resources management leads to higher annual budget for library resources. Overall, while the library staff have become more responsible and enthusiastic in providing services, the students have developed reading habits as well as self-confidence, assertiveness and enthusiasm in doing activities both inside and outside the school.